Sociology of crime, law and deviance. Vol. 2 - Ulmer, Jeffery T., 1966- (Stamford, Ct. : JAI Press, 2000. Elsevier : Architectural Press, 2000)
"Sociology of Crime, Law and Deviance" is an annual series of volumes that publishes scholarly work in criminology and criminal justice studies, sociology of law, and the sociology of deviance and social control. These are very broad topics, and the series reflects this breadth. The series includes theoretical contributions, critical reviews of literature, empirical research, and methodological innovations. The series especially showcases "big picture" pieces that review and critically reconceptualize what is known and what remains to be understood about broad directions of research and theorizing about crime, justice, law, deviance, and social control. In addition, the series showcases a diversity of methodological approaches. "Volume 2" demonstrates such methodological diversity by presenting quantitative studies, ethnographies and discourse analyses. Through an application of these methodologies, the authors examine sanctions, crime and fear and legal and social control organizations and processes. The volume concludes with four chapters contributing to theory development.
When does race matter? An analysis of conditions under which race affects sentence severity / Miriam DeLone -- Implications of ghetto-related behavior for a community and crime model: defining the process of cultural attenuation / Pamela Wilcox Rountree -- Policing, culture, and fear in the Korean American community / Min Sik Lee -- Markets for legal services and the rise of franchise law firms / Jerry Van Hoy -- Transformation of the oral tradition of the police subculture through the introduction of information technology / Albert J. Meehan -- A duty to kill: an occupational perspective from the front lines of a killing institution / Elizabeth McLin -- Legitimating murder? An analysis of newspaper coverage of violence at abortion clinics / Gray Cavender -- Reading prisons: a metaphoric-organizational approach / Christopher R. Williams -- Impeachment work in the Menendez brothers' murder trial: the interactional achievement of facticity, credibility, and accountability / Stacy Burns -- Deficiencies in the sociology of sex work / Ronald Weitzer -- Crime in high places: a criminological perspective on the Clinton case / David O. Friedrichs -- Beyond black and white: ethnoviolence between oppressed groups / Barbara Perry -- Explaining violence, substance abuse, and persistent violence among men: elaborating a side-by-side integrative model of four theoretical perspectives / Rebecca S. Katz.
Description based on print version record.
Keywords: Criminal law; Deviant behavior; Crime -- Sociological aspects; Crime & criminology; Social Science -- Criminology; Electronic books